1997
DOI: 10.1620/tjem.183.55
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Evaluation of Lower Uterine Segment to Predict the Integrity and Quality of Cesarean Scar during Pregnancy: A Prospective Study.

Abstract: A prospective randomized study was conducted to measure the serial thickness of the lower uterine segment (LUS) by transvaginal ultrasonography in a control group of 80 women having no history of uterine surgery and in a study group of 43 women having a history of previous cesarean section (C/S). In the study group, more than 2 mm of thickness of the LUS was considered as good healing and less than 2 mm of thickness as poor healing. After serial sonographic examination, the women with good healing were given t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
54
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 12 publications
4
54
0
Order By: Relevance
“…Our finding of a difference in LUS thickness between the cesarean and control groups is similar to the findings of Gotoh et al 9 and Qureshi et al, 13 which showed that the LUS was thinner in women with previous cesarean delivery than in the control groups. However, the parity factor had not been examined in those studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our finding of a difference in LUS thickness between the cesarean and control groups is similar to the findings of Gotoh et al 9 and Qureshi et al, 13 which showed that the LUS was thinner in women with previous cesarean delivery than in the control groups. However, the parity factor had not been examined in those studies.…”
Section: Discussionsupporting
confidence: 91%
“…It is therefore obvious that the techniques used for measuring the LUS thickness and identifying uterine defects have not been consistent among different studies. Although some studies seem to give good results with different measurement techniques, 11,13,15 our experience suggests that measurement of only the myometrial layer should be more representative of the LUS thickness because 13.2% of our patients showed thickening of the LUS scar at the outer layer but thinning of the underlying myometrial layer. In addition, measurements that include the bladder mucosa and the underlying tissues are more likely influenced by the variation of the bladder size.…”
Section: Discussionmentioning
confidence: 80%
“…At the opening of the abdominal wall during CS, surgeon made an objective evaluation of the integrity and thickness of the LUS, as described by Qureshi et al [13]. The LUS was graded as follows: Grade I (LUS was well developed), Grade II (LUS was thin without visible content), Grade III (LUS was translucent with visible content), and Grade IV (LUS had well-circumscribed defects, either dehiscence or rupture).…”
Section: Methodsmentioning
confidence: 99%
“…Based on the previous studies [13][14][15][16], a sample size of 34 women in each group was required to compare the difference in mean LUS thickness, for an a of 0.05 and a power of 0.80, with an anticipated difference in mean LUS thickness of 0.4 mm and an anticipated SD of 0.8 mm. Considering 10 % rate of spontaneous labor before surgery and any loss to follow up, a total of 50 women were selected in each group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation